Social network services applied to social intervention - Castillo-de-Mesa, Joaquín (My University, 2017)
Since the appearance of the internet, the metaphor of networks has inundated every corner of reality, whether ‘offline’ or ‘online’. The online social system presents new relational possibilities for every type of activity, whether between groups of persons or organizations. At the current stage of internet consolidation, services found on online social networks have emerged, enabling people to connect in new ways. Such services provide opportunities for all activities involving communication and the exchange of information. Sharing, cooperating, coordinating and exchanging information and resources are collective actions facilitated by the existence of tools and services provided by new technological mediums.
Keywords: Redes sociales; Social innovation; Social media; Social intervention; social networks; Communities